The Relationship Between Wind and Rain in the Qur’an: Thematic Interpretation Approach and Meteorological Analysis - Rohmawati, Fithriya Yulisiasih; Alim, Ahmad Syahirul (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Wind and rain are natural phenomena around us that are considered normal. In fact, both can only happen with the power of Allah SWT, humans are unable to intervene in it. Scholars have interpreted verses related to wind and rain from a linguistic perspective, but this is not enough to explain this phenomenon more fully. This research was prepared as an effort to complete thematic interpretation studies to reveal the relationship between wind and rain in the Al-Quran using a scientific interpretation method approach and meteorological analysis. The method used is literature study by referring to the tafsir of al-Thabari, Ibn Kathir and al-Tantawi as well as scientific articles in the field of meteorology. The results of the study show that; There are seven verses in the Koran regarding wind (al-Riyah) which are related to rain. Not all wind is related to rain. Wind can help the process of forming clouds and moving clouds, help the rotation of the rainy season, and be a source of information about the rainy season or daily rain events. However, there are interpretations from several Muslim scholars that are not in accordance with current meteorological studies. This is possible due to limited knowledge when the interpretation was made or limited understanding and references by the author more broadly in the field of meteorology.